A study to evaluate prevalence of thrombocytopenia in antenatal patients - Vineetha, Avula; Bhavani, Kesavarapu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Basically, thrombocytopenia is a hemorrhagic disorder that occurs as a result of reduced platelet counts and this study provides a concise over view about the challenges faced with the antenatals who suffer from thrombocytopenia and related issues. it usually results from various etiological factors which demand proper monitoring and timely management for better maternal and Fetal outcomes. this study focuses on the diagnosis of thromobocytopenia and the causes of it and also the effects. Methods: Data are collected from both the antenatal women attending outpatient and inpatient department at obstetrics and gynecology department at Narayana Medical College and Hospital, Nellore with total platelet count less than 1,50,000/ul and then they are followed and the details regarding antenatal complications, intrapartum events and fetal outcome are collected from them. Results: Present study showed that the definite increased risk of preeclampsia, eclampsia, anemia, hypothyroidism, gestational diabetes mellitus, chronic hypertension, overt diabetes, obesity, preterm labor, cesarean section rate, low birth weight babies in elderly primigravidas and anemia, hypothyroidism, preterm labour, low birth babies, NICU admission in teenage primigravidas compared with pregnant in the younger age group. Conclusions: Timely identification and management of the cause of thrombocytopenia is crucial in the antenatal group of women. Most of the cases of thrombocytopenia are incidental findings with asymptomatic patients. Proper diagnosis and timely interventions are essential for better outcomes in antenatals with thrombocytopenia. gestational thrombocytopenia appears to be the most prevalent causes.